2016
DOI: 10.1002/anie.201508249
|View full text |Cite
|
Sign up to set email alerts
|

Hexasubstituted Benzenes with Ultrastrong Dipole Moments

Abstract: Hexasubstituted benzenes have been synthesized with the highest known dipole moments, as determined by dielectric spectroscopy and DFT methods. Based on the preparation of 4,5-diamino-3,6-dibromophthalonitrile, combined with a novel method to synthesize dihydrobenzimidazoles, these benzene derivatives have dipole moments in excess of 10 debye. Such dipole moments are desirable in ferroelectrics, nonlinear optics, and in organic photovoltaics. Structure determination was achieved through single-crystal X-ray cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 34 publications
1
61
0
Order By: Relevance
“…In the crystal lattice of Ag-H4,t here are two independent structures (Ag (1) -H4 and Ag (2) -H4). [8] . [12f] As inferred from the specific angles of Figure 1.…”
Section: Resultsmentioning
confidence: 75%
“…In the crystal lattice of Ag-H4,t here are two independent structures (Ag (1) -H4 and Ag (2) -H4). [8] . [12f] As inferred from the specific angles of Figure 1.…”
Section: Resultsmentioning
confidence: 75%
“…4). A molecular dipole moment for compound 4c was calculated at 3.1 D and can be compared for example to 1,2,4,5-tetrafluorocyclohexane ( 2 , 5.2 D) [18]. …”
Section: Resultsmentioning
confidence: 99%
“…The search for new and more diverse polar hydrophobic scaffolds is attractive for drug discovery research and new materials [18]. In our own lab we have been exploring the synthesis and properties of differently fluorinated aliphatic structures based on the cyclopentane ( 1 ) and cyclohexane ( 2 and 3 ) rings, compounds which can show quite large dipole moments depending on the stereochemistry [1920] (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Among the polymer acceptors in this study, PNDITCVT-R showed the highest Δµ ge of 23.53 D, with large dipole moments in both the ground and excited states of 4.31 and 26.21 D, respectively. [22] With these large Δµ ge values of PNDITCVT-R, more polarized excitons can be produced and the electron-hole separation distance increased, resulting in reduced exciton binding energy. The higher Δµ ge values are attributed mainly to the asymmetric chemical structure of TCVT and the presence of the electronwithdrawing cyano groups.…”
Section: Dipole Moment Change (δµ Ge )mentioning
confidence: 99%